Análisis de los factores que determinan el costo de producción y su incidencia en la toma de decisiones de la Empresa Divertidísimo de Palmira Valle del Cauca (2022)
This research paper analyzes the factors that determine the cost of production in the gelatin cakes business unit under the methodology of costs for production orders in the company Divertidísimo, dedicated to the elaboration of totally natural gelatin cakes.